How manipulation of playing area dimensions in ball possession games constrains physical effort and technical actions in under-11, under-15 and under-23 soccer players. - Nunes, Nuno (2020)
The aim of this study was to investigate the effects of playing area manipulation (20 × 15 m, 25 × 20 m and 30 × 25 m) on external workloads (total distance covered, distance covered while walking, running and sprinting, number of sprints, maximum sprint speed), internal load perceptions (rating of perceived exertion) and techni- cal actions of passing (number of passes with dominant and non- dominant foot, and maximum passing speed) during 4v4 ball pos- session small-sided and conditioned games in under-11, under-15 and under-23 soccer players. Results showed higher values in the large playing area for under-11 in the distance covered in different speed zones, sprint number and RPE (all p <.001) for under-15 in sprints number (p <.01) and maximum sprint speed (p =.02), and for under-23 in both RPE and sprint numbers (p <.01). Although no significant differences were found on technical actions, it was still possible to notice some effects through pairwise comparison. High- intensity running was promoted on larger playing areas, where under-11 s were also able to perform more technical actions of passing. Opposite, under-23s were able to perform more passing on smaller playing areas, where under-11 s perceived the exercise more intense. The impact of different playing areas was reduced for the under-15.